2015
DOI: 10.1007/s00586-015-3844-y
|View full text |Cite
|
Sign up to set email alerts
|

Impaired bone mineral density as a predictor of graft subsidence following minimally invasive transpsoas lateral lumbar interbody fusion

Abstract: Patients with DEXA T scores less than -1.0 who undergo stand-alone LLIF are at a much higher risk of developing graft subsidence. Further, they are at an increased risk of requiring additional surgery. In patients with poor bone quality, consideration could be made to supplement the LLIF cage with posterior instrumentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 34 publications
3
80
0
Order By: Relevance
“…Osteoporotic bone is believed to be at risk of subsidence, screw loosening and fusion failure [3032]. In our study, the average bone mineral density change was −2.01 ± 1.28.…”
Section: Discussionmentioning
confidence: 51%
“…Osteoporotic bone is believed to be at risk of subsidence, screw loosening and fusion failure [3032]. In our study, the average bone mineral density change was −2.01 ± 1.28.…”
Section: Discussionmentioning
confidence: 51%
“…Tempel et al in 2015 reviewed patients who underwent lateral lumbar interbody fusion to find an association between preoperative DEXA scores and interbody subsidence. 15 They found a subsidence rate of 78% in patients with low bone density ( T score less than −1.0) as compared to a subsidence rate of 22% in patients with normal bone density ( T score greater than −2.0), and this was statistically significant. Although subsidence is associated with nonunion and a return of preoperative pain, this study does not fully evaluate fusion rates.…”
Section: Resultsmentioning
confidence: 92%
“…Tempe et al, and other studies, have shown that low bone mass leads to higher rates of subsidence of interbody devices. 7,12,13,15,30 Although this is not a direct evaluation of fusion rates, it can be inferred that the lack of stability will likely lead to nonunion. The study by Schrieber et al found a correlation between low bone mass, as measure by Hounsfield units, and lower fusion rates.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,23 Another pathology-related criterion has been studied in LLIF subsidence: poor bone quality. Similarly to the present study, Tempel et al 18 conducted a case-control study to analyze bone mineral density (BMD) in cases that evolved with subsidence following LLIF. They found that a DEXA T score of less than -1.0 predicts subsidence, with sensitivity and specificity of 78.3 and 63.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…12,14,17 Based on this data, the use of 22mm or even wider cages is now recommended. Even more recent evidence has revealed that impaired bone quality 18 and inadvertent intraoperative endplate damage 19,20 can contribute to a poorer outcome. Despite the lack of research on cage settling issues, the case selection for standalone LLIFs that do not evolve to subsidence needs elucidation; the objective of this work was to identify the factors correlated with lack of cage subsidence in standalone LLIF procedures.…”
Section: Introductionmentioning
confidence: 99%